Effects of Grammar Teaching Materials Developed for Teaching Turkish as Foreign Language on Achievement and Writing Competence - Memiş, Muhammet Raşit (Bartın Üniversitesi, 2017)
When studies which aim to provide teaching materials needed for both instructing grammar topics and improving language competences in the process of teaching Turkish as foreign language, are analyzed, the most important deficiency is that developed materials have not been tested in terms of functionality, in other words, have not been confirmed with regard to influence on achievement by using these materials in teaching process. In this research basing upon mentioned problem, it is aimed to find out effectiveness, efficiency and influence on achievement of teaching materials developed for using in teaching Turkish as foreign language. With limited words in the sense of this study's scope, the purpose of this research is to present whether materials enriched with animations in the topic of adverbs have impact on academic achievement of Turkish learners as foreign language or not and variance between groups happens with regard to use of what is learnt in writing competence at the end of implementation or not. This research designed with control group posttest experimental model, carried out 32 (16 experimental, 16 control) Turkish language learners who are in 2 different B1 level class selected randomly. According to research results; posttest scores of learners in experimental group who learn adverbs with the materials prepared by researcher are higher than points of students in control group who went with the course book on adverbs and this variation between experimental and control groups is significant. When effect of score variation occurred between groups on achievement is calculated, it is determined that independent variable has quite big impact on success. In accordance with another outcome from research; it is detected that learners in experimental group used more adverbs than students in control group as writing. These results show that materials used during instruction of experimental group, affect academic achievement positively in the topic of adverbs and enhance it; instruction via the materials prepared by researcher, contribute to improvement of learners' writing competence in point of ability to use adverbs.

Türkçenin yabancı dil olarak öğretimi sürecinde gerek dil becerilerinin geliştirilmesi gerek dil bilgisi konularının öğretimi için ihtiyaç duyulan öğretim materyallerini hazırlamak amacıyla yapılan çalışmalar incelendiğinde göze çarpan en önemli eksiklik geliştirilen dil bilgisi öğretim materyallerinin işlevselliğinin denenmemiş olması başka bir deyişle gerçek öğretim süreci içerisinde kullanılarak etkisinin tespit edilmemiş olmasıdır. Bahsedilen bu problemi temele alan bu araştırmada yabancı dil olarak Türkçe öğretimi sürecinde kullanılmak üzere geliştirilen materyallerin etkililiğini, yetkinliğini ve başarıya etkisini ortaya çıkarmak hedeflenmektedir. Çalışma kapsamı açısından daha sınırlandırılmış bir ifadeyle bu araştırmanın amacı, zarflar konusunda animasyonla zenginleştirilmiş materyallerin yabancı dil olarak Türkçe öğrenen bireylerin bu konudaki akademik başarısına etkisi olup olmadığını ve uygulama sonunda üretim becerilerinden yazma sırasında öğrenilenlerin kullanımı noktasında gruplar arasında herhangi bir değişim yaşanıp yaşanmadığını ortaya koymaktır. Gerçek deneme modellerinden sontest kontrol gruplu model ile desenlenen bu araştırma tesadüfi olarak seçilmiş B1 düzeyindeki iki farklı sınıfta Türkçe öğrenen 16'sı deney, 16'sı kontrol grubu olmak üzere toplam 32 öğrenci ile gerçekleştirilmiştir. Araştırma sonuçlarına göre; araştırmacı tarafından geliştirilen materyallerle zarfları öğrenen öğrencilerin sontest puanlarının öğretim seti ile eğitim alan kontrol grubunun puanlarından daha yüksek olduğu ve gruplar arasında oluşan bu farkın anlamlı bulunduğu ortaya çıkmıştır. Gruplar arasında oluşan puan farkının başarı üzerindeki etkisi istatiksel olarak hesaplandığında bağımsız değişkenin başarı üzerinde oldukça yüksek düzeyde etkisi olduğu tespit edilmiştir. Araştırmada elde edilen bir diğer sonuca göre; deney grubunda yer alan öğrencilerin yazılı anlatımlarında kontrol grubu öğrencilerine göre daha çok sayıda zarf kullandıkları belirlenmiştir. Bu sonuçlar deney grubunun eğitim sürecinde kullanılan materyallerin zarflar konusunda akademik başarıyı olumlu yönde etkileyip artırdığını; araştırmacı tarafından geliştirilen öğretim materyaliyle yapılan eğitimin öğrencilerin yazma becerilerinin gelişimine zarfları kullanabilme becerisi bakımından katkı sağladığını göstermektedir.
Yabancı Dil Olarak Türkçe Öğretimi Sürecinde Kullanılmak Üzere Geliştirilen Dil Bilgisi Materyallerinin Akademik Başarı ve Yazma Becerisi Üzerindeki Etkisi